Water Stable Isotopes in Ecohydrological Field Research: Comparison Between In Situ and Destructive Monitoring Methods to Determine Soil Water Isotopic Signatures - Kübert, Angelika; Paulus, Sinikka; Dahlmann, Adrian; Werner, Christiane; Rothfuss, Youri; Orlowski, Natalie; Dubbert, Maren (Frontiers in Plant Science, 2020)
Ecohydrological isotope based field research is often constrained by a lack of temporally explicit soil water data, usually related to the choice of destructive sampling in the field and subsequent analysis in the laboratory. New techniques based on gas permeable membranes allow to sample soil water vapor in situ and infer soil liquid water isotopic signatures. Here, a membrane-based in situ soil water vapor sampling method was tested at a grassland site in Freiburg, Germany. It was further compared with two commonly used destructive sampling approaches for determination of soil liquid water isotopic signatures: cryogenic vacuum extraction and centrifugation. All methods were tested under semi-controlled field conditions, conducting an experiment with dry-wet cycling and two isotopically different labelling irrigation waters. We found mean absolute differences between cryogenic vacuum extraction and in situ vapor measurements of 0.3-14.2‰ (δ18O) and 0.4-152.2‰ (δ2H) for soil liquid water. The smallest differences were found under natural abundance conditions of 2H and 18O, the strongest differences were observed after irrigation with labelled waters. Labelling strongly increased the isotopic variation in soil water: Mean soil water isotopic signatures derived by cryogenic vacuum extraction were 11.6±10.9‰ (δ18O) and +61.9±266.3‰ (δ2H). The in situ soil water vapor method showed isotopic signatures of -12.5±9.4‰ (δ18O) and +169.3±261.5‰ (δ2H). Centrifugation was unsuccessful for soil samples due to low water recovery rates. It is therefore not recommended. Our study highlights that the in situ soil water vapor method captures the temporal dynamics in the isotopic signature of soil water well while the destructive approach also includes the natural lateral isotopic heterogeneity. The different advantages and limitations of the three methods regarding setup, handling and costs are discussed. The choice of method should not only consider prevailing environmental conditions but the experimental design and goal. We see a very promising tool in the in situ soil water vapor method, capturing both temporal developments and spatial variability of soil water processes.